Increasing Teacher Skills In Writing Assessment Instruments Through Assessment Supervision - Marianti Marianti (STKIP Rokania Pasir Pangaraian, 2022)
This study aims to find information about the level of teacher skills in writing asesment instruments with asesment supervision. The design of this research is qualitative research using descriptive method. The object of this research is the teachers of SDN 001 Kabun. The data in this study were obtained from the results of the supervision of the asesment process and all the results of writing the asesment instrument. Data collection in this study was carried out by the researchers themselves using observation techniques, using notes, and cameras. To validate the data in this study using the Triangulation technique. Through asesment supervision techniques, senior teachers can guide other teachers in need. Teachers are motivated to learn and strive to achieve further success. Based on the category of abilities that have been determined in this study, it turns out that for each cycle the results of the teacher's abilities always increase, so that the objectives of this study are achieved, namely teachers who achieve activity abilities and writing skills results 76% of the existing teachers. From these results, it can be concluded that the asesment supervision technique can improve teacher asesment writing skills